Effect of Planting Distance on Nitrogen Uptake and Productivity of Paddy Var. Rojolele Irradiated with Gamma Rays in Inceptisol - Amri Amanah; Sri Nuryani Hidayah Utami; Makruf Nuruddin (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2017)
The objective of this study was to examine the effect of planting distance of paddy var. Rojolele planted in conventional legowo system and dosage of gamma rays irradiated on nitrogen uptake and productivity of paddy. The experiment was arranged in a randomized complete block design (RCBD) with twelve treatments and three replications. The first factor was gamma ray radiation, consisted of three levels, namely control seed (B0), seed irradiated with gamma rays of 200 gray (B2), and seed irradiated with gamma ray of 300 gray (B3). The second factor was planting distance, consisted of four levels, namely distance of 25 x 25 (J1), distance of 30 x 30 (J2), legowo system of 2 : 1 (J3), and legowo system of 4 : 1 (J4 ). The results showed that jajar legowo system with planting distance of 2 : 1 significantly affected the nutrient content of nitrogen in shoot, nitrogen uptake of plant, and yield per hectare. Paddy var. Rojolele irradiated by 300 gray produced higher nitrogen content in shoot, nitrogen uptake of plant, and yield per hectare than those in control seeds and seeds irradiated with 200 gray. There was a tendency that planting distance with jajar legowo system resulted in higher grain (yield), on the contrary, the narrow row spacing impacted on lower grain (yield).